THE ROLE OF VILLAGE OWNED BUSINESS ENTITIES (BUMDES) ON RURAL ECONOMIC DEVELOPMENT IN TANJUNGSARI DISTRICT, SUMEDANG REGENCY - Justinia Castellani; Sasa S. Suratman; gugum Mukdas Sudarjah; Dimas Fajar Muharam; Mochammad Ridwan (JEES: Journal of Economic Empowerment Strategy, 2022)
development should be pursued in order to improve the quality of life and community welfare. One thing that is needed to accelerate the economic growth of rural communities is to establish a Village Owned Enterprise (BUMDES). This study aims to determine the role of village-owned enterprises (BUMDES) on village economic development in Tanjungsari District, Sumedang Regency. This study used a qualitative research method with a descriptive approach, the data used in this study was primary data. The results showed that there were differences in income. village communities before and after the existence of BUMDES, while the condition of BUMDES in 5 villages has been running well and continues to develop, BUMDES in Tanjungsari District has also been able to absorb labor, although not optimally.